2015
DOI: 10.1128/aem.02590-14
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diverse Endophytic and Soil Fusarium oxysporum Populations Associated with Field-Grown Tomato Plants

Abstract: The diversity and genetic differentiation of populations of Fusarium oxysporum associated with tomato fields, both endophytes obtained from tomato plants and isolates obtained from soil surrounding the sampled plants, were investigated. A total of 609 isolates of F. oxysporum were obtained, 295 isolates from a total of 32 asymptomatic tomato plants in two fields and 314 isolates from eight soil cores sampled from the area surrounding the plants. Included in this total were 112 isolates from the stems of all 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 40 publications
4
41
0
Order By: Relevance
“…The diversity of endophytic fungi found in this study in the roots of tomato is in accordance with the general pattern of (Kim et al 2007;Demers et al 2014). All isolates belonged to the phylum Ascomycota.…”
Section: Diversity Of Root Endophytessupporting
confidence: 63%
See 1 more Smart Citation
“…The diversity of endophytic fungi found in this study in the roots of tomato is in accordance with the general pattern of (Kim et al 2007;Demers et al 2014). All isolates belonged to the phylum Ascomycota.…”
Section: Diversity Of Root Endophytessupporting
confidence: 63%
“…These results are consistent with other reports in which several endophytic Fusarium species were isolated from roots in which tomato was shown to be a potential host. Demers et al (2014) assessed the diversity of tomato associated with FOSC populations within tomato fields and, similar to the results in this study, found that members of the F. oxysporum species complexes (FOSC) were the most common Fusarium species detected.…”
Section: Diversity Of Root Endophytessupporting
confidence: 54%
“…Endophytes are microorganisms that asymptomatically colonize the internal tissues of almost all plants (6,7). Our previous studies have demonstrated that the endophytes inside A. lancea grown in the Maoshan area are more abundant than those inside A. lancea grown in other areas (8)(9)(10), and several endophytes, such as Acinetobacter sp.…”
mentioning
confidence: 99%
“…Fungal strains of the genus Fusarium can be found in symbiotic associations with the internal tissues of most plants (Demers et al, 2015;Singh et al, 2015). However, these strains can also act as pathogenic fungi (Sobowale et al, 2005), triggering Fusarium wilt, or fusariosis, which is characterized by xylem hypertrophy (Pinto et al, 2010) and wilting followed by death of the affected plants (Costa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%